Tradisi Bada Kupat dalam Budaya Jawa di Kelurahan Penanggo Jaya Kecamatan Lambandia Kabupaten Kolaka Timur - Febri Krinasnawati; Nurtikawati; Shinta Arjunita Saputri; Elmy Selfiana Malik (Jurusan Tradisi Lisan, Fakultas Ilmu Budaya, Univeritas Halu Oleo, 2023)
The Bada Kupat tradition (eid ketupat) is a tradition carried out by the people of Banyuwangi, East Java, who live in the village of Penanggo Jaya. This tradition is held on the 7th of Shawwal after Eid al-Fitr every year. The purpose of this study is to describe the process of implementing the bada kupat tradition in Penanggo Jaya Village and the meaning contained in the implementation of the bada kupat tradition in Penanggo Jaya Village. In this study, data collection was carried out by means of observation, interviews and documentation. The technique of determining the informants in this study used a purposive sampling technique. The data were analyzed using the following techniques: data presentation, data reduction, data verification and drawing conclusions. The results of this study indicate that the process of carrying out the bada kupat tradition consists of (1) the preparation stage, at this stage consisting of preparing tools and materials to carry out the bada kupat tradition, the process of making diamonds, there are 2 types of ketupat made namely onion ketupat and sinto ketupat ( Java), the process of making lepet as a side dish for ketupat and the process of making young jackfruit vegetables (Don't be fussy). (2) The implementation stage of the ater - ater, where at this stage after the ketupat and its accompanying food are ready to be served, it will be delivered or distributed to the family and neighbors around. (3) The final stage, in the final stage, salvation is carried out as a closing activity in the implementation of the bada kupat tradition and carrying out prayer together and eating together. In the bada kupat tradition, it contains meaning in every stage of its implementation, namely expressing gratitude, giving alms and friendship